Incidence of methicillin-resistance and macrolide-lincosamide-streptogramin B resistance in a clinical sample of Staphylococcal isolates: a pharmacodynamic study - Lafi, Majid A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: a rapid and accurate identification of Methicillim-Resistant Staphylococci (MRS) is of a particular clinical significance because they have cross-resistance to other antibiotics with high ability to be transmitted among hospitalized patients known as epidemic MRS. Objectives: the detection of MRS and the susceptibility of isolates to antimicrobial agents, also to determine inducible and constitutive macrolide-lincosamide-streptogramin B (MLSB) resistance mechanisms by pharmacodynamic interpretative reading approaches. Methods: standard disk diffusion method was performed for 30 Staphylococcus aureus and 10 Staphylococcus epidermidis isolated from wound, burn patients admitted to Ramadi General Hospital in Ramadi and eczema patients who attended the same hospital, from September 2005 to April 2006, against oxacillin 5µg disk and cefoxitin 30µg disk as indicators to detect the presence of MRS, and against selected antimicrobial agents, double disk tests (D-test) were performed to determine MLSB-inducible resistance mechanism. Results: out of 40 isolates, 34 (85%) isolates considered to be MRS according to cefoxitin susceptibility results, but according to interpretative reading of -lactams susceptibility pattern with oxacillin 24 (60%) of isolates identified to be MRS. High percentage of isolates were non-susceptible to β-lactam antibiotics and 4 (10%) isolates were resistant to imipenem, also 4 (10%) isolates were resistant to vancomycin, the interpretative reading of the susceptibility pattern against erythromycin and clindamycin showed classical 21/40 (52.5%), MLSB-inducible 6/40 (15%, +ve D-test), MLSB-constitutive 6/40 (15%), and macrolide efflux-mechanism 7/40 (17.5%, -ve D-test). Conclusion: high percentage (85%) of isolates was MRS, and 15% of them have MLSB-inducible and another 15% have MLSB-constitutive resistance mechanisms inferring the presence of erm gene, 17.5% may have macrolide efflux-mechanism encoded by the msrA gene. The presence of such resistance mechanisms implicates serious problem in hospital regarding control of infection and control of antibiotic use; thus, necessitate an appropriate protocol (to implement) for the control of infection and use of antibiotics.